The Study of Policy Implementation: Does Special Autonomy Represent the Papuans Aspiration? - Ismoyo, Muhammad Bayu; Pratama, Yudha; Irianto, Ahmad (Bestuurskunde: Journal of Governmental Studies, 2022)
Special autonomy is a political consensus on the desire of the Papuans to live in prosperity by considering their indigenous rights. Two decades of the implementation of Special Autonomy for Papua, it is still considered ineffective to answer the crucial demands, such as political rights, material welfare, and indigenous participation in the development. Political participation of Papuan indigenous (OAP) is expected as the main issue of which has crucially affected the mandatory aspects, such as political conductivity, development objectivity, social welfare, and security. This research aims to figure out the importance of political participation to the OAP and how it can affect the special autonomy enforcement in Papua. The results show that political participation of Papua considerably contributes to the local institutional involvement, addressing political conductivity, directing the development target, and realizing the deliberative policy. In other findings, political supervision is highly required to be evaluated in ensuring the optimizing of political participation for OAP.